NILAI – NILAI KEKERABATAN DALAM NOVEL PEREMPUAN KEMBANG JEPUN: SEBUAH KAJIAN ANTROPOLOGI - Wiwik Sari Dewi Nigraheni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2015)
Education should be done thoroughly, that besides the cognitive factors take into account so do the affective factor of students. Affective factor is a susceptibility factor that is one students' sense of self, others and the environment. For that students need to be introduced to the science that can be honed sense, the science literature. So that students not only develop intellectually, but also emotionally evolved.This research aim is to describe the language, history, tradition and values education literature in Perempuan Kembang Jepun Novel written by Lan Fang. The object of this research is the text of the novel. The theories used include literature anthropology approach and value education.the conclusion of this research that students can learn cultural family relationship and the norm or rules among family, love, peace and tolerance.Keywords : Literature of Anthropology, Family’s Values.